Antimicrobial effects of Coleus amboinicus, Lour folium infusum towards Candida albicans and Streptococcus mutans - Devi Rianti; Sri Yogyarti (Dental Journal (Majalah Kedokteran Gigi), 2006)
A laboratory experimental study conducted on antimicrobial effects of Coleus amboinicus, Lour folium Infusum towards Candida albicans and Streptococcus mutans (S. mutans). Effective concentration of Coleus amboinicus, Lour to decrease the quantities Candida albicans and S. mutans colonies is expected to be found out in this study. This study was using Coleus Amboinicus, Lour folium infusum with 12.5%, 15%, 17.5%, 20%, and 22.5% concentrations. Sterilized aquadest used as a control. Candida albicans and S. mutans quantities was enumerated by counting the amount of Candida albicans and S. mutans growth in the Sabouraud ,s dextrose agar and Tryptone and yeast Agar media, using Colony Forming Unit per milliliter (CFU/ ml) unit. Data analysis was using a One-Way ANOVA and LSD with 5% degree of significance. The result showed 22.5% concentration of CAL folium infusum was the most effective in decreasing the quantity Candida albicans and S. mutans colonies.